Life Experiences which Shape Dual Roles of Indonesian Women: A Phenomenological Study of Entrepreneur and Educator Figures (International Journal of Scientific Research and Management (IJSRM), 2018)
This study aims to gain a deep understanding of life experiences of the Indonesian women entrepreneur and educator figures in carrying out their dual roles by applying phenomenological research method. Research participants were Indonesian women figures who are not only considered success in their profession but also in family life, which make them being recognized by the society. Drawing on data collected from semi-structured in-depth interviews supported by an examination of documents and observation. Using interpretative phenomenological analysis, the findings in this study explore that the experience of life in their family, school, and the community before their marriage form dual roles of women entrepreneurs and educators figures. Meanwhile, the experiences of having variety of roles in the family, workplace, and society environment form the dual roles of women figures in this study after their marriage. Based on the results of this study suggests, among others, the importance of giving a woman a chance to study both formal and non formal even after she married. This study is limited to the women figures who work as an entrepreneur and an educator. So that research on women figures in other professions is very recommended.